Protection of personal data in the system of modern accounting in the context of the implementation of the Regulation of the European Parliament and of the EU Council 2016/679 of 27 April 2016 - Świetla, Katarzyna (Ochrona danych osobowych w systemie współczesnej rachunkowości w kontekście implementacji Rozporządzenia Parlamentu Europejskiego i Rady (UE) 2016/679 z dnia 27 kwietnia 2016, 2019)
This article is an attempt to analyze the existing solutions in the field of the protection of personal data. Training and advisory materials on this subject prepared by numerous law firms (32) were analyzed, providing a valid explanation, understanding and implementation of the new obligations in the field of data protection. In addition the author conducted pilot interviews in accounting offices (17) concerning the protection of personal data to indicate the approach of service providers to the performance of the tasks in the field of personal data protection. The key findings of the study are: noticeable increase in the interest of the contracting parties in data protection issues, as well as presenting their positive aspects along with possible problems in their practical application. An important contribution of the author is also the presentation of the key points of agreements which the parties should pay attention to in order to avoid misunderstandings
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 3, s. 59-71
Keywords: accounting; accounting services; data protection; behavior of service providers; rachunkowość; usługi księgowe; ochrona danych; zachowania usługodawców